Parents' Parenting Pattern Description Ofslow Learner Children In Pandemic Situation Coronavirus Disease 19 - Dea Adhe Rizky; Nadhirotul Laily; Muhimmatul Hasana (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This study examines "The Overview of Parenting Patterns for Slow Learner Children in a Coronavirus Disease 19 Pandemic Situation". The selection of parenting patterns used in caring for slow learner children is indeed very important for the survival of the slow learner child's life. The aspects and factors that exist in this study determine the parenting style of the five subjects. This research uses descriptive qualitative research using data as a tool used to solve the problems that occur. The measuring instrument used is expected to be able to obtain accurate data and be able to dig deeper into other data. The results of this study are the five subjects using democratic parenting as the choice of parenting for slow learner children. The choice of democratic parenting is an effective thing in raising slow learner children. This was proven at the time of the interview and the grouping of the interview results based on the defined concept limits. Cultural factors in this study lead to the parenting pattern used by the subject's parents, until now some have been applied and some have replaced them with new parenting patterns. The factors of parental education in these five subjects are not very influential. Parents with low education still want the best for their children's education later. Socio-economic factors do not really affect the existing parenting. The impact resulting from this parenting pattern is that children tend to become more confident individuals, children are easy to interact and socialize with the environment even though it takes some time for it. However, children become individuals who understand the conditions and circumstances of their parents because their parents often provide understanding in certain situations. During the coronavirus disease 19 pandemic like this, parents are required to be teachers of their respective children, because the implementation of online schools is still valid today. It is hoped that further researchers will be able to provide an effective way for online learning as it is today.